Incidence and Recovery of Vocal Fold Immobility Following Pediatric Cardiac Operations. Issue 4 (July 2021) - Barr, Jennifer M.; Bowman, Kandice; Deshpande, Monica; Dewey, Elizabeth N.; Milczuk, Henry A.; Vo, Johnson; Shen, Irving; Muralidaran, Ashok
Background: Loss of laryngeal function after congenital cardiac surgery causes morbidity and prolongs hospitalization. Early diagnosis of vocal fold immobility (VFI) and referral to pediatric otolaryngology (pOTO) aids in laryngeal rehabilitation. Understanding the incidence and recovery rates of VFI enables counseling for families of infants undergoing high-risk surgery. Methods: A retrospective chart review from November 2014 to July 2019 of infants postcardiac surgery where the aortic arch or surrounding structures were manipulated and were screened via flexible fiberoptic laryngoscopy (FFL) at a single institution was performed. Patients were divided into five surgical categories: Norwood procedure, aortic arch augmentation via median sternotomy, arterial switch operation, coarctation repair via lateral thoracotomy, and cardiac surgeries including ligation of a patent ductus arteriosus (PDA). Patients undergoing isolated PDA ligation were excluded. Results: One hundred ninety-nine qualifying operations occurred during this period; 28 patients did not undergo FFL before discharge and were excluded from the analysis. Immediately following cardiac surgery, 34% (58 of 171 patients) had VFI. Follow-up was completed by 38 of 58 patients with VFI. Complete recovery was demonstrated in 63% (24 of 38) of patients by 6 months and in 86% (33 of 38) within 18 months. The highest risk occurred with the Norwood procedure and arch augmentation via median sternotomy. Conclusions: Infants undergoing surgery involving the aortic arch and surrounding structures have high rates of VFI. Follow-up by pOTO is recommended to optimize laryngeal rehabilitation. Most patients have spontaneous recovery within 18 months of cardiac surgery.